Vision Therapy Procedures for Tunneling. - Getzell, Jeffrey H. (Optometry & Visual Performance, 2015)
Tunneling is a form of an exclusive concentration and is a common spatial adaptation. Treatment strategies for tunneling and the overall visual process will be addressed. Strategies include diaphragmatic breathing, syntonics, and vision therapy activities that stress working in real space with lenses and prisms. Objectives, observations, expected responses, modifications, and questions for the patient are discussed for each vision therapy activity.